The Great Impostor: Transaminitis Masking the Coinfection of Syphilis and Human Immunodeficiency Virus - Sunit Tolia; Hassan Kassem; Ana Capatina-Rata (Case Reports in Medicine)
Introduction. The incidence of syphilis continues to rise in the United States over the past 15 years. This disease process is classified into stages and may present with a coinfection of Human Immunodeficiency Virus (HIV). Case Report. We present a case of a 32-year-old African American male who presented with cutaneous manifestations of secondary syphilis and transaminitis. A workup revealed that the transaminitis was secondary to underlying syphilitic hepatitis in the presence of HIV coinfection. The patient had a reactive rapid plasma reagin (RPR) of 1 : 64 TU and reactive Treponema pallidum particle agglutination assay (TPPA). Lab findings showed alkaline phosphate (ALP) of 648 unit/L, aspartate aminotransferase (AST) of 251 unit/L, and alanine aminotransferase (ALT) of 409 unit/L. Conclusion. Syphilitic hepatitis is a recognized entity in the medical literature. It is a manifestation of secondary syphilis and it is more commonly seen in coinfected patients with both syphilis and HIV. Therefore, primary care physicians should keep infectious etiologies (e.g., syphilis and HIV) in the differential diagnosis of patients who present with unexplained liver dysfunction in a cholestatic pattern.